2017
DOI: 10.1016/j.canep.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Implementing community-based cervical cancer screening programs using visual inspection with acetic acid in India: A systematic review

Abstract: The objective of this review was to systematically appraise the existing published literature about community-based cervical cancer screening programs that have used visual inspection methods using acetic acid (VIA) in India. All peer reviewed journal articles till December 2015 were searched per PRISMA guidelines. Articles reporting results from cervical cancer screening programs in community-based settings, conducted in India, and using VIA were included in this review. The search resulted in 20 articles to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 42 publications
0
40
0
Order By: Relevance
“…However, compared with the interest in screening technologies, there has been less effort to understand the cervical cancer continuum of care and the barriers to screening and follow-up. 16 - 20 This is a gap in knowledge, because multiple factors along the continuum of care affect the effectiveness of screening programs, regardless of the underlying technology. 21 …”
Section: Introductionmentioning
confidence: 99%
“…However, compared with the interest in screening technologies, there has been less effort to understand the cervical cancer continuum of care and the barriers to screening and follow-up. 16 - 20 This is a gap in knowledge, because multiple factors along the continuum of care affect the effectiveness of screening programs, regardless of the underlying technology. 21 …”
Section: Introductionmentioning
confidence: 99%
“…Screening with VIA is still the most cost-effective and efficient method of cervical cancer screening in resource-poor countries, however, because it is highly subjective and dependent on training and continued supervision, sensitivity in detecting grade 2 or higher lesions has been reported anywhere from 7.7% to 82.6% compared to care HPV, a low-cost same day testing that has sensitivities above 70%. Screening for HPV offers a more objective approach, and an opportunity to increase screening coverage through self-collection [32,33].…”
mentioning
confidence: 99%
“…A secondary aim is to demonstrate the feasibility and highlight the operational logistics of conducting community‐based screening of eligible women and follow‐up of screened women—vital information that is often missing from surveillance studies . The team conducting the screening clinics were trained in overseeing and managing community‐based work and were composed of several members, each with a distinct role.…”
Section: Discussionmentioning
confidence: 99%
“…Country level estimates, however, suggest that the coverage of cervical cancer screening in developing countries is on average 19% compared with 63% in developed countries . Studies from India have identified barriers on several socioecological levels such as lack of knowledge, personal disbelief in prevention of cancer, lack of care‐seeking when asymptomatic, lack of money for treatment, and reduced access to healthcare services . There is evidence that women in low‐resource settings find pelvic exams to be embarrassing, painful, and uncomfortable; therefore, they prefer the self‐sampling option …”
Section: Introductionmentioning
confidence: 99%